Enhancing thermal and mechanical properties of polypropylene using masterbatches of nanoclay and nano-CaCO3: A review - Chafidz, Achmad (Communications in Science and Technology, 2018)
Polymer nanocomposites (PNCs) can be considered as promising relatively new types of composite materials. PNCs give opportunity to develop new composites materials with different structure-property relationships compared to their conventional micro/macro scale composites. Polyolefin based nanocomposites nowadays become more important, because this type of composites has been largely used in various industries. For example, polypropylene based nanocomposites have been widely used in automobile – related industries to replace their conventional composites. This review paper will focus on the polypropylene based nanocomposites prepared using masterbatches of nanoclay and nano-CaCO3 via melt compounding method. The thermal and mechanical properties of such nanocomposites were also discussed.